The Effect of Teaching Social Sciences Using the Zahorek Model on the Achievement Motivation of Second-grade Intermediate Students (Journal of the College of Basic Education, 2022)
The current research aims at knowing the effect of teaching social studies using the Zahorek model on the achievement motivation of the second- grade intermediate students. The research sample consists of (63) students, the research sample was distributed into two groups, with (32) students in the experimental group and (31) in the control group, and by verifying the null hypothesis : (there are no statistically significant differences at the level (0.05) between the average scores of the experimental group students who study social sciences using the Zahorek model, and the average scores of the control group students who study the same subject in the usual way in the achievement motivation, the research is limited to second-grade intermediate students in the intermediate and morning high schools for boys affiliated to the General Directorate of Education in Baghdad / Al-Rusafa 1 for the academic year (2020-2021). The results show that the students of the experimental group who study the social subject with the Zahorek model surpassed the students of the control group who study the same subject in the traditional way in terms of achievement motivation.